Redes locales y espacios globales: Macao y Marsella en una perspectiva comparada para el análisis de la divergencia económica entre China y Europa (s. XVIII) - Pérez García, Manuel (2016)
In the current essay perceptions and dialogues between China and Europe are observed by analysing concrete geopolitical areas which developed trade, international relations and socioeconomic networks between China and Europe. We focus on a particular study case: Macau, connecting with South China and the Manila-Acapulco trade routes during the early globalization integrating western and eastern markets; and Marseille, in Mediterranean Europe connecting with eastern markets. Such concrete comparison might enrich the great divergence debate with the aim of observing asimetric economic growth models of China and Europe through the analysis of trade networks and changes on consumer behaviour.